Preperation of Materia and Their Chemical, Physical and Electrical Analysis for HEV - Gill, Satpreet Singh; Kurre, Manish (International Journal of Computer Sciences and Engineering, 2019)
Electrical and electrochemical properties of PEO based hot pressed nanocomposite polymer electrolyte (NCPE) membrane (1-x)[70PEO:30AgNO3]:xTiO2 where x=0-20 wt% , casted by using a novel hot pressed technique for prperation of electrochemical devices viz. supercapacitor, battery etc. have been studied. Solid Polymer Electrolyte (SPE) composition (70PEO:30AgNO3) reported earlier identified as highest conducting film at room temperature, has been used as 1st phase host matrix and nano-size (~8nm) filler TiO2 as 2nd phase dispersion. As a consequence of dispersal in SPE host, highest conductivity was achieved in at 5wt% of TiO2. This composition has been referred as optimum composing composition (OCC). Addition of KOH is OCC shows further increase in conductivity. The ion transport behavior in NCPE membrane have been discussed on the basis of ionic conductivity(σ), ionic transferred number(tion) and activation energy Ea. Morphology study and compositional veriation also performs by SEM.